1994
DOI: 10.1007/bf01858103
|View full text |Cite
|
Sign up to set email alerts
|

The Children's Headache Assessment Scale (CHAS): Factor structure and psychometric properties

Abstract: This study investigated the content validity, factor structure, and psychometric properties of the Children's Headache Assessment Scale (CHAS), a parent rating scale for identifying environmental variables associated with pediatric headache. In Study 1, input from physicians and psychologists was obtained to develop a revised set of 44 items receiving high endorsement. In Study 2, the questionnaire was administered to parents of 92 child headache sufferers, ages 6-16, and readministered 2 weeks later. An explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…First, previous studies on asthma in which parents used the same rating scales have found that asthma severity in children is influenced by heredity (21) and is significantly correlated with the frequencies of early and recent respiratory infections and with the impact of respiratory infection as a trigger of asthma episodes (30). Second, other research has shown that parent reports regarding their children's episodic illnesses, such as headache and asthma, are reliable and valid (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…First, previous studies on asthma in which parents used the same rating scales have found that asthma severity in children is influenced by heredity (21) and is significantly correlated with the frequencies of early and recent respiratory infections and with the impact of respiratory infection as a trigger of asthma episodes (30). Second, other research has shown that parent reports regarding their children's episodic illnesses, such as headache and asthma, are reliable and valid (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, headache-specific scales are increasingly being developed for the purposes of assisting in the diagnosis of headache (e.g., Labbé et al, 1985;Mindell & Andrasik, 1987), identifying environmental variables associated with headache (Budd, Workman, Lemsky, & Quick, 1994), and assessing impact of headache on various important life domains (quality of life) and extent of disability (Andrasik, 2001b;D'Amico et al, 2003;Hershey et al, 2004;Powers, Patton, Hommel, & Hershey, 2004).…”
Section: Standardized Approaches To Assessmentmentioning
confidence: 99%